Virtual reality and behaviour management in paediatric dentistry: a systematic review - Diana Xavier de Barros Padilha; Nélio Jorge Veiga; Anna Carolina Volpi Mello-Moura; Patrícia Nunes Correia (BMC, 2023)
Abstract Background Virtual reality (VR) has emerged as an innovative tool in medicine and dentistry, improving anxiety and pain management in children. The immersive and interactive environments of VR technology facilitate positive engagement of young patients during dental procedures via distraction, potentially reducing anxiety levels and improving treatment experience. The aim of this review was to provide current evidence-based guidance on the usage of VR in the clinical practice of paediatric dentistry. Methods A systematic review was conducted according to the PRISMA guidelines with the following research question using the PICO format: Does VR (I) effectively manage anxiety and pain (O) during a paediatric dental consultation (P) compared to alternative behavioural control techniques (C)? PubMed/Medline®, SCOPUS and Web of Science databases were searched and analysed. Results A total of 22 randomised control trials were included in this review. These studies have shown that VR is a highly effective method of behaviour management, successfully alleviating pain and anxiety in children during dental treatment, surpassing traditional tools. Selected studies included participants with a large age range and dental procedures varied greatly, from first consultations to infiltration of local anaesthetic and other invasive procedures. VR was mostly used during treatment delivery and different immersive VR techniques were considered. Behaviour, anxiety and pain scales were used to determine efficacy and patient satisfaction. Conclusions VR offers an engaging and immersive experience, effectively diverting patients' attention away from the clinical environment, fostering a positive and enjoyable treatment experience. However, it is important to acknowledge the limitations of existing studies and the need for further research to enhance the understanding of VR's full potential in paediatric dentistry.